Gender Role Attitudes and Religiosity among Higher Education Students - Fényes, Hajnalka (Journal for the study of religions and ideologies, 2020)
Besides demographic and social background determinants, religiosity is one of the most important factors which influence attitudes towards gender roles. In Europe, egalitarian gender roles have been aided by the eventual ubiquity of wide-ranging freedoms, women's increasing labour force participation in the post-socialist regions, the drastic decline in fertility, and state-sponsored secularisation. In this study, we examine Hungarian higher education students' views on gender roles using a nation-wide sample (N=1502, 2017). We create a typology with two modern attitude types beside the traditional view on gender roles, namely the pragmatic-instrumental and postmaterialist-postmodern types. We employ multinomial regression to analyse the factors which increase the likelihood of each type's occurrence. After accounting for the effect of demographic and social factors, we find that religiosity has a significant impact on the acceptance towards traditional gender roles. In addition, we also record the novel finding that respondents are much likelier to belong to the postmaterialist-postmodern type, which approves of women's labour force participation and favours the father's involvement in the family, if they are religious in the sense that they follow the teaching of a church.